Analisa Kestabilan Transien Pada Jaringan Listrik 150KV Di Gardu Induk Waru - Aswin Dwi Rochman; Gatut Budiono; Reza Sarwo Widagdo (Politeknik Kampar, 2023)
The occurrence of transient disturbances in the power network can be influenced by several factors, including when a short circuit occurs, motor starting, natural factors and sudden addition of load, which causes frequency instability on the bus. As in this study, an additional load of 10%, 20% and 30% for each feeder can cause transient disturbances which cause frequency stability on the 150kV bus. Frequency experiences instability when there is a transient disturbance caused by an additional load. By simulating using the Etap software, each feeder is given an additional load of 10%, showing a normal state. The 50Hz frequency experiences instability down to 47Hz and stabilizes again at 230 seconds. Hz and rose again at 245 seconds, and when given an additional load of 30% the frequency which was originally 50% experienced instability down to 47.5Hz and stabilized again at 230 seconds.